A comparative assessment of combustion behavior and emissions characteristics of DI diesel engine fueled with waste plastic oil and eucalyptus biofuel for sustainable development applications. (31st December 2022) - Naima, Khatir; Bousbaa, Hamza; Ahmad, Hijaz; Al-Bahrani, Mohammed; Tarabet, Lyes; Menni, Younes; Lorenzini, Giulio
Abstract: The increase in population growth rates led to a high rate of production and use of plastic materials, which created a problem in the collection and management of this waste [1 ]. This created severe threats to the environment and the ecosystem. The main objective of this paper is to conduct an experimental assessment of a direct diesel engine fueled with waste plastic oil (WPO), eucalyptus biofuel (EB) and conventional diesel. The engine operated in the same operating condition with all fuels. The results show that WPO has a shorter ignition delay, resulting in lower in-cylinder temperature and pressure than EB and diesel fuel. The brake thermal efficiency of WPO is significant over all the range of engine loading. Carbon monoxide emissions of WOP fuel are lower than diesel fuel and higher than EB oil. Nitrogen oxide emissions of WPO are lower at low and full loads but higher at medium load. Considerable decrease in unburned hydrocarbons and particulate matter emissions with EB compared with WPO and diesel fuels. The results of this study concluded that both fuels are considered a viable solution for achieving sustainably.